Epistemologias do ser-estar professor de matemática no curso de pedagogia de Rondônia : realidades, desafios e possibilidades explicitadas em um simpósio temático imaginado - Navarro, Érica Patrícia (2021)
The present work sought to know / recognize aspects present in the narratives of the teachers who form the Pedagogy classroom courses, who work in the initial training, with mathematics subjects and / or their methodologies, with the central region of the state of Rondônia as an outline. As for the structuring and presentation of the work, our thesis was built using creative writing. The First Meeting of Trainers of Trainers: The Nature of the Mathematics Educator – Accounts of Imagined Debates was designed and held, a meeting real time, imaginary time between the trainers in the central region of the state of Rondônia. Our source of inspiration was the creative and engaging writing of Hoisel (1998) and Lakatos (1978), which allowed us to create this environment of reality and inventiveness. Our work presents the narratives of the trainer teachers, interacting in the symposium as active participants in the conversations, this interaction made it possible to understand how their professional profile was constituted until then. Based on their life and training histories, it was possible to perceive their epistemological bases as a teacher and mathematician, their perceptions as a teacher trainer. Thus, we confirm our thesis that the narratives of teachers who train Pedagogy courses in the Central Region of the State of Rondônia express indicators of aspects of the epistemological profile of Mathematics assumed by teacher trainers that come from their constitution and teacher training; this is because the epistemological treatment given to mathematics in usual classes is a reflection of teacher education, action and reflection as impacting factors in the mathematical formation of teachers in the early years. The writing of this text constituted a construction of the reality established in the research, with a view to organizing the argument supported in this doctoral text and was validated by the ideas, concepts and propositions based on real authors and enunciated based on interviews with real people, whose narrative structure was imagined for the setting to be constituted. The deponent subjects, the testimonies and the authors represent the real ones; the events organized in its sessions are the imaginaries, the organization of the testimonies and the conduct of the writing process are complex. Regarding the theoretical support, we base ourselves on Tardif (2014), Zabalza (2017), Gauthier (2013), Becker (2013), Machado (1989), Poincaré (1995), Bruter (1998), Davis and Hersh (1986) , Silva (2007), these and other authors who deal with studies in the area of teacher education, epistemology of mathematics, teaching knowledge and knowledge inherent to the teaching of the teacher trainer served as a reference. Methodologically, it is a qualitative approach research. The interviews conducted with the trainers were based on the comprehensive interview by Kaufmann (2013) and for the analysis we used the Ethnomethodology and Conversation Analysis of Watson and Gastaldo (2015).